Ultra‐low Mass Sputtered and Conventional Catalyst Layers on Plasma‐etched Nafion for PEMFC Applications. Issue 6 (25th October 2017) - Omosebi, A.; Besser, R. S.
Abstract: This paper presents performance results for the use of plasma‐etched Nafion membranes to suppress polarization losses in proton exchange membrane fuel cells (PEMFCs) configured from 0.1 mg cm −2 conventional Pt/C dispersion and 0.02 mg cm −2 ultra‐thin sputter‐deposited Pt catalyst layers. Four MEA configurations, namely, etched membrane‐conventional electrode, pristine membrane‐conventional electrode, etched membrane‐sputter electrode, and pristine membrane‐sputter electrode cells were explored, and their respective maximum power densities were ∼514.6, 417.9, 170.1 and 138.3 mW cm −2 . The results demonstrated that independent of MEA fabrication approach, cells with O2 plasma treated membranes had reduced ohmic resistances and delivered superior performance over their pristine counterparts, validating the utility of membrane etching for achieving improved PEMFC performance.